ASSESSMENT OF SOME HEAVY METAL CONCENTRATION IN WINTER WHEAT CROP (Triticum aestivum l.) GROWN IN SOIL AROUND INDUSTRIAL AREA WITHIN DUHOK CITY, KURDISTAN REGION OF IRAQ - zebari, biryar; Musher R. Ahmed Albarwary (Science Journal of University of Zakho, 2025)
Wheat (Triticum aestivum L.) is a crucial staple grain for global food security, but the accumulation of harmful trace metals can compromise its safety. This study investigated the concentrations of copper (Cu), cadmium (Cd), zinc (Zn), and lead (Pb) in wheat grains and soil from various locations near an industrial area in Duhok City, from February and June 2024. The metal concentrations in wheat grains were found to range from 0.539±0.0231 to 1.035±0.0028 mg/kg for lead, 0.417±0.0085 to 0.5666±0.0063 mg/kg for zinc, 0.2203±0.0033 to 0.2723±0.0016 mg/kg for copper, and 0.004±0.001 to 0.0293±0.0038 mg/kg for cadmium., The result showed that the levels of Zn, Cu, and Cd in wheat grain were within the permissible limit according to the World Health Organisation WHO Codex Alimentarius. This suggests that industrial pollutants pose significant health risks to populations living near contaminated environments. The results of agricultural soil samples collected from the industrial area showed that the area has been slightly contaminated with toxic metals. There were considerable variations (P<0.05) in the concentrations of metals across the study locations. P-values for Pb, Zn, Cu, and Cd in both soil and wheat grains indicate that industrial emissions and transformation are significant sources of contamination